Positional control of pneumatic manipulators for construction tasks - Rachkov, M. Yu. (2002)
This paper describes solutions that can be applied to pneumatic manipulator problems in positioning, both for angle trajectories and for long linear trajectories, used in construction tasks. Optimal positioning of a pneumatic manipulator along angle trajectories with minimum control energy consumption is given. The implementation of the control system is presented. Control algorithms for a long linear trajectory manipulator based on two-phase and three-phase motion modes of the end-effector are investigated. Conventional and fuzzy logic controls of a pneumatic manipulator were applied and experimental testing was carried out. The obtained results allow widening the application range of pneumatic manipulators in construction, particularly in gantry type machines.